Externalizing behavior in healthy young adults is associated with lower cortisol responses to acute stress and altered neural activation in the dorsal striatum. (5th September 2021) - Konzok, Julian; Henze, Gina‐Isabelle; Peter, Hannah; Giglberger, Marina; Bärtl, Christoph; Massau, Claudia; Kärgel, Christian; Schiffer, Boris; Eisenbarth, Hedwig; Wüst, Stefan; Kudielka, Brigitte M.
Abstract: The externalizing spectrum is characterized by disinhibition, impulsivity, antisocial‐aggressive behavior as well as substance (mis)use. Studies in forensic samples and mentally impaired children suggested that higher rates of externalization are linked to lower cortisol stress responses and altered affect‐related neural activation. In this fMRI‐study, we investigated whether externalizing behavior in healthy participants is likewise associated with altered cortisol responses and neural activity to stress. Following a quasi‐experimental approach, we tested healthy participants ( N  = 61, 31 males) from the higher versus lower range of the non‐clinical variation in externalization (31 participants with high externalization) as assessed by the subscales disinhibition and meanness of the Triarchic‐Psychopathy‐Measure. All participants were exposed to Scan STRESS, a standardized psychosocial stress paradigm for scanner environments. In both groups, Scan STRESS induced a significant rise in cortisol levels with the high externalization group showing significantly lower cortisol responses to stress than the low externalization group. This was mainly driven by males. Further, individual increases in cortisol predicted neural response differences between externalization groups, indicating more activation in the dorsal striatum in low externalization. This was primarily driven by females. In contrast, post‐hoc analysis showed that hypothalamic‐pituitary‐adrenal axis hyporeactivity in males was associated with prefrontal and hippocampal activation. Our data substantiate that individuals from the general population high on externalization, show reduced cortisol stress responses. Furthermore, dorsal striatum activity as part of the mesolimbic system, known to be sensitive to environmental adversity, seems to play a role in externalization‐specific cortisol stress responses. Beyond that, a modulating influence of gender was disclosed. Abstract : According to the ontogenic process model of the externalizing spectrum by Beauchaine et al. (2016), abnormalities in neural activation (e.g., prefrontal areas, amygdala) and hypothalamic‐pituitary‐adrenal axis function may be responsible for externalizing symptoms. However, within the non‐clinical range, mechanisms remain still unclear. In healthy participants with high versus low externalization, we could show that individual increases in cortisol predicted neural response differences between externalization groups, indicating more activation in the dorsal striatum in low externalization.